The geological setting of arsenic enrichment in groundwater of the shallow aquifers of the Tista Floodplain, Rangpur, Bangladesh - Saha, Sudip; H.M. Selim, A.; Kanti Roy, Mrinal (International Journal of Advanced Geosciences, 2020)
Arsenic is present in water samples within the studied active floodplain areas of the Tista river, Rangpur Division, Bangladesh. All the water samples contain less arsenic than the WHO prescribed limit of 10 Î¼g/L. 93.33% groundwater samples have higher Mn content than the permissible limit of 0.01 mg/L of WHO. The heavy metal concentrations of water can be expressed as Fe>Mn>Zn>As on the basis of their mean content. The heavy metals are negatively correlated with the well depth which is indicative of the influence of the anthropogenic activities on the concentrations of heavy metals. The arsenic concentration in water samples is higher in the central part of the study area. The coarser grain size, dominance of physical weathering, elevated topography and the effective flushing of groundwater resulted low concentration of arsenic in the groundwater. The EDS study reveals that arsenic occurs as coating materials of the silicate minerals. The river waters also have arsenic content lower than WHOs permissible limit. The factor analysis reveals that the iron and arsenic is released by the chemical weathering of arsenic bearing minerals like pyrite and arsenopyrite. The Fe and Mn derived in the groundwater by the chemical weathering of iron and manganese bearing minerals such as iron rich clay, silicate minerals and iron sulfides.Â Â